2005
DOI: 10.4141/s04-062
|View full text |Cite
|
Sign up to set email alerts
|

Using multivariate adaptive regression splines (MARS) to identify relationships between soil and corn (Zea mays L.) production properties

Abstract: . 2005. Using multivariate adaptive regression splines (MARS) to identify relationships between soil and corn (Zea mays L.) production properties. Can. J. Soil. Sci. 85: 625-636. Over-application of agricultural fertilizers can contribute to degradation of surface water quality. Factors governing crop establishment and yield must be identified in order to efficiently manage N application rates in corn (Zea mays L.) production systems. Spatial data sets of corn establishment and grain yields, and soil physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Based on the reported importance of micro-topographic attributes on crop growth properties [18,19,23], we included Lidar-derived variables to represent the micro-topography of the fields over this low topographic relief study area. Lidar data were collected over the experimental site by GeoDigital (Sandy Springs, GA) in November 2011, and a 1-m spatial resolution digital terrain elevation dataset was derived from the Lidar point cloud using LAStools (rapidlasso GmbH, Gilching, Germany).…”
Section: Lidar and Topographic Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the reported importance of micro-topographic attributes on crop growth properties [18,19,23], we included Lidar-derived variables to represent the micro-topography of the fields over this low topographic relief study area. Lidar data were collected over the experimental site by GeoDigital (Sandy Springs, GA) in November 2011, and a 1-m spatial resolution digital terrain elevation dataset was derived from the Lidar point cloud using LAStools (rapidlasso GmbH, Gilching, Germany).…”
Section: Lidar and Topographic Derivativesmentioning
confidence: 99%
“…At this scale, our results showed the importance of variables related to the canopy and surface structure, the SR index and slope, respectively. These structural variables contain implicit information on spatial patterns of soil, water and nutrient distributions [23], which can ultimately affect crop yield. In 2011, for example, the ANN models underestimated soybean yield in most of the eastern fields of the study area.…”
Section: Predicted Within-field Corn and Soybean Yieldsmentioning
confidence: 99%
“…A spline is a utility defined piecewise by polynomials, and it is applied to a class of functions used in input-output data interpolation [28]. A common spline function is the cubic spline or knote [43].…”
Section: Multivariate Adaptive Regression Splines (Mars)mentioning
confidence: 99%
“…First, the forward algorithm chooses all possible fundamental functions and their related knots. Second, the backward algorithm gets rid of all basic functions in order to produce the best combinations of existing knots, and, finally, the smoothing operation is performed to obtain continuous partition borders [43].…”
Section: Multivariate Adaptive Regression Splines (Mars)mentioning
confidence: 99%
“…Multivariate Adaptive Regression Spline (MARS) approach has also proved to be an important methodology to identify and correlate yield and variables impacting crop production (Emamgolizadeh et al, 2015;Zabihi et al, 2019). Turpin et al (2005) has identified dominant factors affecting corn establishment and grain yields using MARS automated regression data mining method. Their study concluded that soil water content and cone penetration resistance are key parameters than elevation and mineralizable soil nitrogen in predicting crop establishment and grain yield.…”
Section: Learning) With Modern Agricultural Technologymentioning
confidence: 99%